Eye movement abnormalities in essential tremor versus tremor dominant Parkinson's disease. Issue 5 (May 2019) - Visser, F.; Bour, L.J.; Lee, Y.X.; ten Brinke, T.R.; van Rootselaar, A.F.
Highlights: Saccade features differ between essential tremor (ET) and tremor dominant Parkinson's disease (PD-T). Both patient groups have a reduced sustained smooth pursuit eye movements gain. Eye movement abnormalities reflect cerebellar dysfunction in ET and basal ganglia pathology in PD-T. Abstract: Objective: To show that eye movement abnormalities differ between essential tremor (ET) and tremor dominant Parkinson's disease (PD-T), and that these abnormalities reflect cerebellar dysfunction in ET and basal ganglia pathology in PD-T. Methods: In this exploratory study, in 23 patients with ET, 21 age-matched patients with PD-T, and 19 age-matched healthy controls (HCs), we investigated visually guided saccades, antisaccades, and smooth pursuit eye movements (SPEM). Results: While the ET group had a normal gain (saccade amplitude/target amplitude) and latency of saccades, the PD-T group had hypometric visually guided saccades, and a prolonged latency of visually guided saccades and antisaccades. The SPEM gain was similarly low in both ET and PD-T and was significantly lower in both patient groups than in the HC group. Conclusions: In ET, SPEM gain was reduced in the presence of normal saccades, whereas in PD-T, the reduced SPEM gain was accompanied by delayed saccade initiation and hypometric saccades, in line with cerebellar dysfunction in ET and basal ganglia dysfunction in PD-T. Significance: These findings support the presumed cerebellar pathology in ET. In addition, the difference in saccade features may contribute to the groundwork for a quantitative diagnostic test to differentiate between these disorders.